Resource-aware task scheduling by an adversarial bandit solver method in wireless sensor networks - Khan, Muhidul Islam (© 2016 Springer International Publishing, 2016)
This article was published in the Eurasip Journal on Wireless Communications and Networking [©2016 Springer International Publishing.] and the definite version is available at: http://dx.doi.org/10.1186/s13638-015-0515-y. The article website is at: http://jwcn.eurasipjournals.springeropen.com/articles/10.1186/s13638-015-0515-y